Crosslinking of Chitosan with Dialdehyde Derivatives of Nucleosides and Nucleotides. Mechanism and Comparison with Glutaraldehyde. (3rd March 2016) - Mikhailov, Sergey N.; Zakharova, Alexandra N.; Drenichev, Mikhail S.; Ershov, Andrey V.; Kasatkina, Mariya A.; Vladimirov, Leonid V.; Novikov, Valentin V.; Kildeeva, Natalia R.
ABSTRACT: In medical and pharmaceutical applications, chitosan is used as a component of hydrogels–macromolecular networks swollen in water. Chemical hydrogels are formed by covalent links between the crosslinking reagents and amino functionalities of chitosan. To date, the most commonly used chitosan crosslinkers are dialdehydes, such as glutaraldehyde (GA). We have developed novel GA like crosslinkers with additional functional groups–dialdehyde derivatives of uridine (oUrd) and nucleotides (oUMP and oAMP)–leading to chitosan-based biomaterials with new properties. The process of chitosan crosslinking was investigated in details and compared to crosslinking with GA. The rates of crosslinking with oUMP, oAMP, and GA were essentially the same, though much higher than in the case of oUrd. The remarkable difference in the crosslinking properties of nucleoside and nucleotide dialdehydes can be clearly attributed to the presence of the phosphate group in nucleotides that participates in the gelation process through ionic interactions with the amino groups of chitosan. Using NMR spectroscopy, we have not observed the formation of aldimine bonds. It can be concluded that the real number of crosslinks needed to cause gelation of chitosan chains may be less than 1%.